Anti‐Aggregation of Nanosized CoS2 for Stable K‐Ion Storage: Insights into Aggregation‐Induced Electrode Failures (Adv. Energy Mater. 29/2022). Issue 29 (4th August 2022) - Zhang, Hehe; Cheng, Yong; Sun, Jingjie; Ye, Weibin; Ke, Chengzhi; Cai, Mengting; Gao, Haowen; Wei, Ping; Zhang, Qiaobao; Wang, Ming‐Sheng
Abstract : Potassium‐Ion Batteries In article number 2201259, Ming‐Sheng Wang and co‐workers reveal the mechanism of the aggregation of nanosized anode materials upon potassiation by in/ex‐situ electron microscopies, which is found to be a crucial reason for serious electrode failures. An anti‐aggregation strategy is further proposed through isolating the nanoparticles inside individual carbon nanoshells, which prevents their extensive aggregation across the electrode, resulting in superior electrochemical stability.